Over work : transforming the daily grind in the quest for a better life - Schulte, Brigid, 1962- (Henry Holt and Company, 2024)
"From the New York Times bestselling author of Overwhelmed, a deeply reported exploration of why American work isn't working and how our lives can be made more meaningful Following Overwhelmed, Brigid Schulte's groundbreaking examination of time management and stress, the prize-winning journalist now turns her attention to the greatest culprit in America's quality-of-life crisis: the way our economy and culture conceive of work. Americans across all demographics, industries, and socioeconomic levels report exhaustion, burnout, and the wish for more meaningful lives. This full-system failure in our structure of work affects everything from gender inequality to domestic stability, and it even shortens our lifespans. Drawing on years of research, Schulte traces the arc of our discontent, from a time before the 1980s, when work was compatible with well-being and allowed a single earner to support a family, until today, with millions of people working multiple hourly jobs or in white-collar positions where no hours are ever off-duty. She casts a wide net in search of solutions, exploring the movement to institute a four-day workweek, introducing Japan's Housewives Brigade-which demands legal protection for family time-and embedding with CEOs who are making the business case for humane conditions. And she demonstrates the power of a collective and creative demand for change, showing that work can be organized in an infinite number of ways that are good for humans and for business. Fiercely argued and vividly told, rich with stories and informed by deep investigation, Over Work lays out a clear vision for ending our punishing grind and reclaiming leisure, joy, and meaning"--